Ionic liquid-based gel polymer electrolyte containing zwitterion for lithium-oxygen batteries. (10th June 2020) - Woo, Hyun-Sik; Son, Hyebeen; Min, Ji-Yun; Rhee, Junki; Lee, Ho-Taek; Kim, Dong-Won
Abstract: The key challenge of high energy density lithium-oxygen batteries is to develop a stable electrolyte system not only to suppress growth of lithium dendrite and solvent evaporation but also to resist the attack by superoxide anion radical formed at the cathode. Gel polymer electrolyte can effectively encapsulate organic solvent in the cell, suppress electrolyte decomposition and provide stable interfacial characteristics with lithium electrode. In this study, a three-dimensional cross-linked poly(methyl methacrylate)-based gel polymer electrolyte (GPE) containing non-volatile ionic liquid and zwitterion was synthesized and characterized for lithium-oxygen batteries. In this GPE, a zwitterion was proved to improve the transport properties of Li + ions and enhance the interfacial stability towards the lithium electrode. As a result, the lithium-oxygen cell assembled with GPE containing ionic liquid and zwitterion exhibited a good cycling stability at a constant current density of 0.25 mA cm −2 . Highlights: Gel polymer electrolyte containing ionic liquid and zwitterion was synthesized. A zwitterion improved the transport properties of Li + ions and interfacial stability. A Li-oxygen cell with gel polymer electrolyte exhibited a good cycling stability.